EFEKTIFITAS KONSELING KELOMPOK PENDEKATAN REALITAS UNTUK MENINGKATKAN MINAT BELAJAR PESERTA DIDIK - Senja Rahma Yona; Muslima Muslima; Barmawi Barmawi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The purpose of this writing is to find out about group counseling the reality approach in overcoming the low interest in learning at learners. The purpose of this discussion is to see the effectiveness of counseling reality approach group to increase participants' interest in learning students. The type of research that researchers use is the type of research quantitative Pre experimental design one-group pre-test and post-test where an experimental group measured the dependent variable then given treatment and re-measured. Population in In this study, there were 93 students in class VIII. Deep sample In this study, 8 people were taken using a random technique sampling, namely taking samples randomly selected based on the results of the pre-test of interest questionnaires that have low learning interest. Instrument The method used is a questionnaire of students' learning interest. From research what researchers did obtained the results of interest in learning group students experiment when pre-test with a total score of 811 with an average score 101 is in the low category. After being given the posttest value treatment for the experimental group with a total score of 1245 and an average score 156, this value has increased and is in the high category. The results of hypothesis testing indicate that the group counseling approach effective reality to increase interest in learning in students.